1987
DOI: 10.1143/jjap.26.1811
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of Switching Behavior in a Ferroelectric Liquid Crystal

Abstract: Simulations of the switching behavior in a ferroelectric liquid crystal were carried out with the model proposed by Handschy and Clark. There appear to be various types of switching processes for changing surface anchoring force. Results of simulations are compared with experimental observations, some of which seem to be well reproduced by the Handschy-Clark model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Molecules switch to W1 -anchoring energy minimum on this surface. The same conclusion was found in references [3,22]. If E does not further increase, the twisted state is induced in large domains of FLC sample.…”
Section: Andsupporting
confidence: 87%
See 1 more Smart Citation
“…Molecules switch to W1 -anchoring energy minimum on this surface. The same conclusion was found in references [3,22]. If E does not further increase, the twisted state is induced in large domains of FLC sample.…”
Section: Andsupporting
confidence: 87%
“…On the other hand, our approach permits comparison of different disclination nucleation mechanisms by using the value of a critical field. In this note we have investigated three nucleation processes characterized by critical fields E:, E,,Il and E §" given by expressions (10), (14) and (22), respectively. It is seen that If an electric field reaches the values E § given by equation (10) the nucleation of the structure with orientation cp = -7r starts at the lower surface where the molecular anchoring with higher energy W2 occurs.…”
Section: Andmentioning
confidence: 99%
“…They are found to have good optical and electrical contrast between the amorphous and crystalline states, and they feature characteristics for phase change memory. [1][2][3] For decades, many efforts have been devoted to investigating the optical or phase change properties of Ge 1 Sb 2 Te 4 or Ge 2 Sb 2 Te 5 (GST) thin films separately. [4][5][6][7][8] However, comparative research on the electrical behavior of Ge 1 Sb 2 Te 4 and Ge 2 Sb 2 Te 5 has rarely been done systematically.…”
Section: Introduction and Experimentsmentioning
confidence: 99%
“…A comparative study on electrical transport properties of thin films of Ge 1 Sb 2 Te 4 and Ge 2 Sb 2 Te 5 phase-change materials Ling Xu, 1,a) Liang Tong, 1 Lei Geng, 1 Fei Yang, 1 Jun Xu, 1 Weining Su, 2 Dong Liu, 1 Zhongyuan Ma, 1 We have investigated the electrical properties of Ge 1 Sb 2 Te 4 and Ge 2 Sb 2 Te 5 thin films in the temperature range of 27 to 200 C. The optical bandgap values obtained from the measured absorption spectra for amorphous Ge 1 Sb 2 Te 4 and Ge 2 Sb 2 Te 5 are 0.70 and 0.90 eV, respectively. The results of the in situ temperature dependence of the sheet resistance demonstrate that both Ge 1 Sb 2 Te 4 and Ge 2 Sb 2 Te 5 thin films in the amorphous phase exhibit a temperature-activated electrical conductivity with activation energy values of 0.42 and 0.45 eV, respectively.…”
mentioning
confidence: 99%
“…For this binary system a wide range of stoichiometries was found that showed the required properties for fast, rewriteable optical data storage. Soon afterwards Yamada and coworkers presented their findings on alloys along the pseudo-binary line between GeTe and Sb 2 Te 3 , in particular Ge 2 Sb 2 Te 5 and described a recorder to utilize the properties of this material class [16]. The identification of materials with fast crystallization also reignited the interest in electronic memories based on tellurides.…”
Section: Introductionmentioning
confidence: 99%